2005
DOI: 10.1212/01.wnl.0000148609.35718.7d
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E for prophylaxis against chemotherapy-induced neuropathy

Abstract: Vitamin E supplementation in cancer patients may have an important neuroprotective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(111 citation statements)
references
References 30 publications
5
102
0
4
Order By: Relevance
“…A randomized pilot trial assessing the effects of vitamin E supplementation on chemotherapy-induced peripheral nerve damage was recently conducted in 31 patients with cancer treated with six courses of cumulative cisplatin, paclitaxel, or their combination regimens [69]. Patients were randomly assigned in two groups and followed by neurologic examination and electrophysiologic study.…”
Section: Vitamin Ementioning
confidence: 99%
“…A randomized pilot trial assessing the effects of vitamin E supplementation on chemotherapy-induced peripheral nerve damage was recently conducted in 31 patients with cancer treated with six courses of cumulative cisplatin, paclitaxel, or their combination regimens [69]. Patients were randomly assigned in two groups and followed by neurologic examination and electrophysiologic study.…”
Section: Vitamin Ementioning
confidence: 99%
“…No differences were seen in tumor weight, growth delay, or survival between the two groups. An additional three reports on the use of vitamin E to reduce chemotherapy toxicity were found [152][153][154]. They were all performed by the same research group and may represent multiple reports on the same patient population, so they will be discussed in aggregate.…”
Section: Neuropathymentioning
confidence: 99%
“…Decreased rate of neuropathy [151][152][153][154] Ginger postoperatively in surgical cancer patients; with MOPP chemotherapy; with cisplatin chemotherapy Decreased nausea [155][156][157] Calendula homeopathic lotion in radiation therapy…”
Section: Grifola Umbellatae In Bladder Cancermentioning
confidence: 99%
“…Although normal pain relief does not reduce the pain associated with CIPN, no specific anti-inflammatory drug has been trialled as a protective agent. This is one of the main mechanisms of action that has been identified in the nutrients and the herbs trialled for CIPN that have shown a possible beneficial protective effect [233][234][235][236][237][238][239][240][241][242][243][244][245][246]. The anti-inflammatory component may or may not protect patients against CIPN but it would be an interesting aspect to investigate.…”
Section: Strengths and Weaknesses And Gaps In The Researchmentioning
confidence: 99%
“…Vitamin E was demonstrated to have positive results in three RCT's showing a significant reduction in the relative risk of cisplatin induced PN, especially ototoxicity [233][234][235][236]254]. However, a phase III multi-centre trial combining vitamin E with taxanes, cisplatin, carboplatin, oxaliplatin or combination concluded that vitamin E did not appear to reduce the incidence of sensory neuropathy [254].…”
Section: Vitamin Ementioning
confidence: 99%